Análisis estadístico de las exportaciones de bienes en la Comunidad Andina, Enero 2010- Junio 2018 - Carranza Trujillo, Mery Rosibeth (2019)
In this descriptive and longitudinal research, the purpose of this research was to perform_x000D_ the statistical analysis of the exports of goods in the Andean Community, January 2010-June 2018, using time series with the Box-Jenkis methodology, obtained from the CAN page - Integrated Foreign Trade System (SICEXT). The Jenkins Box methodology was used, a statistical technique for historical identification, which met the requirements for the respective data analysis. The procedure was performed with the statistical package EVIEWS 10 and EXCEL 2016. Finally, it was concluded that the model identified was a non-stationary series and the forecast model was a model SARIMA (, , )(, , ) without intercept, whose equation was y (equation) being tested for suitability of the model. The forecast was made in the period January to June 2018, the forecasts were evaluated using the Absolute Average Error Percentage (PEMA) is 4.27% which measures the magnitude of forecast errors in percentage average compared to the real values of the series and the Average Percentage of Error (PME) of - 0.04%, it is concluded that the model does not overestimate or underestimate monthly exports in thousands of dollars to the world in the Andean Community